2019
DOI: 10.1016/j.mce.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin and fibrosis: Emerging targets, challenges, and future directions

Abstract: The peptide hormone relaxin is well-known for its anti-fibrotic actions in several organs, particularly from numerous studies conducted in animals. Acting through its cognate G proteincoupled receptor, relaxin family peptide receptor 1 (RXFP1), serelaxin (recombinant human relaxin) has been shown to consistently inhibit the excessive extracellular matrix production (fibrosis) that results from the aberrant wound-healing response to tissue injury and/or chronic inflammation, and at multiple levels. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…A total of 40 signaling pathways were identified. In the most significantly altered signaling pathway in this study, fibrosis was reported in previous studies to be involved in the ‘Hedgehog signaling pathway’ ( 35 37 ), ‘ABC transporters’ ( 38 ), ‘ErbB signaling pathway’ ( 39 , 40 ), ‘cAMP signaling pathway’ ( 41 , 42 ), ‘Relaxin signaling pathway’ ( 43 , 44 ), ‘Ras signaling pathway’ ( 45 , 46 ) and ‘PI3K-Akt signaling pathway’ ( 47 , 48 ). Additionally, six ECM-associated pathways were directly associated with renal fibrosis.…”
Section: Discussionmentioning
confidence: 54%
“…A total of 40 signaling pathways were identified. In the most significantly altered signaling pathway in this study, fibrosis was reported in previous studies to be involved in the ‘Hedgehog signaling pathway’ ( 35 37 ), ‘ABC transporters’ ( 38 ), ‘ErbB signaling pathway’ ( 39 , 40 ), ‘cAMP signaling pathway’ ( 41 , 42 ), ‘Relaxin signaling pathway’ ( 43 , 44 ), ‘Ras signaling pathway’ ( 45 , 46 ) and ‘PI3K-Akt signaling pathway’ ( 47 , 48 ). Additionally, six ECM-associated pathways were directly associated with renal fibrosis.…”
Section: Discussionmentioning
confidence: 54%
“…But we have not been able to examine the efficacy of RLX-2 on pre-existing fibrosis. RLX-2 is expected to use in various fibrous diseases [11], and is also known to enhance heart function with dilating peripheral blood vessels, and clinical research was held as a therapeutic agent for heart failure [46]. Although further study is needed, RLX-2 can be expected to be a new therapy for endometriosis with various effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the endometriosis mouse model (Figure 5a), administration of RLX-2 significantly decreased the area of the endometriotic-like lesion compared to the non-treated control (p = 0.01, Figure 5b). As RLX-2 has an anti-fibrotic potential [11], the extent of fibrosis in the mouse endometriotic-like lesions was evaluated using the Masson trichrome staining method. As shown in Figure 5c, fibrous tissues, which are stained with light blue, were decreased in the RLX-2 group compared to the control.…”
Section: Endometriosis Mouse Model (Endometrial Implantation Mouse Momentioning
confidence: 99%
See 2 more Smart Citations